ABOUT THE IMPORTANCE OF LABORATORY LESSONS IN THE COURSE “CONCEPTS OF MODERN NATURAL SCIENCE” - Bukhman, Lyubov; Bukhman, Nikolay (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Methods of teaching the course “Concepts of modern natural science” are discussed. It is shown that real (not virtual) laboratory practical work is an important and necessary part of this discipline. The example of realization of such laboratory workshop is given in the article. This laboratory workshop consists of two parts, which can be called “physical” and “biological”. The laboratory works of the “physical” part of the workshop are selected in such a way as to demonstrate deep and universal physical concepts on simple examples. For example, the study of polarized light allows students to get acquainted with the concept of spin of a particle on a simple and understandable example. A simple experience with the Magdeburg hemispheres allows us to discuss the relationship between the continual and discrete approach to the theory of the structure of matter. The “biological” part of the workshop includes not only the fundamental problems of biology itself (for example, the problems of reproduction), but also the problems of mineralogy and paleontology. The study of mineralogical samples allows students to better understand the ideas of the evolution of the earth's surface, and the study of paleontology allows a better understanding of the ideas of the theory of biological evolution.